In vitro interaction between Zidovudine and some adsorptive antacids - Okhuelegbe, Eraga Sylvester; Osita, Idemili Nwachukwu; Amara, Iwuagwu Magnus (Dhaka University Journal of Pharmaceutical Sciences, 2015)
The in vitro interaction between zidovudine and three antacids and a commercial product was investigated. The extent of adsorption of zidovudine by the antacids, and the effects of the antacids on the disintegration time and dissolution of the drug from tablets were studied. Adsorption of the drug by the antacids followed the order; magnesium trisilicate > aluminium hydroxide > magnesium hydroxide. Retardation of dissolution amongst the antacids and commercial product was of the order; Jawasil® > magnesium trisilicate > aluminium hydroxide > magnesium hydroxide. Also, the degree of retardation of dissolution from the tablets increased as the amount of adsorbent increased. Co-administration of zidovudine and adsorptive antacid formulations should be avoided in clinical practice since it can lead to a decrease in the bioavailability of zidovudine, ultimately leading to therapeutic failure. DOI: http://dx.doi.org/10.3329/dujps.v13i1.21853 Dhaka Univ. J. Pharm. Sci. 13(1): 1-6, 2014 (June)